Views of Rohingya refugees: engagement and experiences with humanitarian agencies in cox’s bazar, Bangladesh - Centre for Peace and Justice (CPJ), Brac University (Brac University, 2022)
This policy brief, a joint publication by Centre for Peace and Justice, Brac University (CPJ) and The Asia Foundation, conveys findings from a rapid analysis to understand refugees’ perspectives on community engagement and consultation approaches by the humanitarian agencies delivering services and aid in the camps of Cox’s Bazar, Bangladesh. The study’s themes and the research questions were designed by CPJ’s Rohingya research team in response to frequent community concerns, and all viewpoints expressed here are those of camp residents. As an academic institution and knowledge partner serving the humanitarian response, CPJ aims to help diverse stakeholders understand each other’s perspectives.